Uji Bioaktivitas Ekstrak Daun Zodea (Evodia suaveolensSheff)terhadap Hama Gudang Tribolium castaneum(Coleoptera: Tenebrionidae)Herbst. - RIZKY RANDAL CAMERON; ARINAFRIL ARINAFRIL; MULAWARMAN MULAWARMAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2016)
Bioactivity Test of Zodea Leaf Extract (Evodia suaveolens Sheff) on Red Flour Beetle Tribolium castaneum(Coleoptera: Tenebrionidae)Herbst.The study bioactivy of zodea leaf extract on red flourbeetlewas conducted in Laboratory of Entomology, Plant Pest And Disease Department, Faculty of Agriculture, Sriwijaya Universityfrom June to September 2014.E. suaveolensis a native plant from Papua that very well-known as mosquito repellent. The experiment aimed to determined level of repellent various extract concentrations of zodea leaf extract and mortality on T. castaneum. Completely Randomized Design was used in this study with six treatments and four replicates. Concentrations used were 0%, 32,78%, 36,88%, 40,98%, 45,07% dan 49,17% which were obtained from preliminary test results and further more, the result was analyzed by probit analyzed method to determined concentrations would be used. LC50 value was 40,98% and ± 10%. The results was the best treatment on 45,78% with 96,2% and classified very strong repellent index. The lowest repellent index was 32,78% with 89,2% and classified strong repellent index. The highest Mortality of T.castaneumon 40,07% with 17,5% mortality dan the lowest mortality on 0% and 36,88% with no T. castaneum died. LC50 was 87,018%. We could conclude that E. suaveolenspossessed very strong repellent index on T. castaneum, but not effetive to kill T.castaneum.